Chemiluminescence determination of antioxidant property of Zizyphus mistol and Prosopis alba during oxidative stress generated in blood by Hemolytic Uremic Syndrome-producing Escherichia coli - Albrecht, Claudia (2010)
This study was undertaken to elucidate the antioxidant effect of Zizyphus mistol and Prosopis alba, with the hypothesis that these fruits can counteract the induction of reactive oxygen species (ROS) caused by toxins produced by Escherichia coli. In the search of nutrients effective against the Hemolytic Uremic Syndrome (HUS), we detected by chemiluminescence a protective role of both plants, due to their natural antioxidants significantly decreasing the levels of ROS induced by toxins from E. coli in blood. The ferric reducing antioxidant power (FRAP) was found to be higher in Z. mistol than in P. alba. The chemical analyses of the phenols and flavonoids present in the fruit extracts indicated that the FRAP correlated with the amount of phenolic compounds, but not with the flavonoids analyzed. Both fruits studied reduce the induction of ROS, and in this way help to prevent the development of complications related to oxidative stress generated in the blood of patients with HUS. Copyright © 2010 John Wiley & Sons, Ltd.